Bimatoprost 0.03%/timolol 0.5% preservative-free ophthalmic solution versus bimatoprost 0.03%/timolol 0.5% ophthalmic solution (Ganfort) for glaucoma or ocular hypertension: a 12-week randomised controlled trial - Goldberg, Ivan (BMJ Publishing Group, 2014)
AIM: To compare the efficacy and safety of single-dose bimatoprost 0.03%/timolol 0.5% preservative-free (PF) ophthalmic solution with bimatoprost 0.03%/timolol 0.5% ophthalmic solution in patients with open-angle glaucoma or ocular hypertension. METHODS: In this multicentre, randomised, parallel-group study, patients were randomised to bimatoprost/timolol PF or bimatoprost/timolol once daily in the morning for 12 weeks. Primary efficacy endpoints, reflecting differing regional regulatory requirements, included change from baseline in worse eye intraocular pressure (IOP) in the per-protocol population at week 12, and the average eye IOP at weeks 2, 6 and 12 in the intent-to-treat population. RESULTS: 561 patients were randomised (278 to bimatoprost/timolol PF; 283 to bimatoprost/timolol); 96.3% completed the study. Both treatment groups showed statistically and clinically significant mean decreases from baseline in worse eye IOP and in average eye IOP at all follow-up time points (p<0.001). Bimatoprost/timolol PF met all pre-established criteria for non-inferiority and equivalence to bimatoprost/timolol. Ocular adverse events were similar between treatment groups, with conjunctival hyperaemia being the most frequent. Most were mild or moderate in severity. CONCLUSIONS: Bimatoprost/timolol PF demonstrated non-inferiority and equivalence in IOP lowering compared with bimatoprost/timolol, with no significant differences in safety and tolerability. TRIAL REGISTRATION NUMBER: NCT01177098.